Favorable association between early initiation of sodium-glucose cotransporter-2 inhibitors and in-hospital prognosis in acute myocardial infarction - Hung Thanh Quach; Anh Thi Kim Nguyen; Bao Quoc Dinh; Tuan Minh Nguyen; Hoang Huy Bui; Tuan Ngoc Tran; Tien Dung Ho; An Le Pham; Si Van Nguyen (PLoS ONE, 2026)
Introduction Acute myocardial infarction remains a major cause of death and disability worldwide, especially in low- and middle-income countries. Standard early management includes dual antiplatelet therapy, statins, beta-blockers (BB) and renin–angiotensin–aldosterone inhibitors (ACEi/ARB/MRA). Sodium–glucose cotransporter-2 inhibitors (SGLT2i) have been associated with favorable changes in cardiac function in acute myocardial infarction, but their impact on in-hospital mortality has not been well established. Objective To assess the association between early initiation of SGLT2i and in-hospital mortality among patients with acute myocardial infarction. Methods A retrospective, single-center study was conducted on 394 adult patients hospitalized with acute myocardial infarction at Nguyen Trai Hospital, Ho Chi Minh City, between January 2022 and October 2024. The data extraction and analysis were performed from July 31 to October 24, 2024. Patients with incomplete data, secondary acute myocardial infarction, or eGFR < 20 mL/min/1.73 m 2 were excluded. Data from electronic medical records were analyzed. The primary outcome was in-hospital mortality. Logistic regression was used to identify independent predictors. Results Mean age was 66.0 ± 11.7 years; 57.1% were male. SGLT2i was initiated within 24 hours of admission in 23.9% of patients. In-hospital mortality occurred in 53 patients (13.5%). In multivariable analysis, lower left ventricular ejection fraction (OR 0.91, 95% CI: 0.85–0.97; p = 0.003) and sepsis (OR 5.14, 95% CI: 1.04–25.36; p = 0.04) were independently associated with in-hospital mortality. In addition, use of BB/ACEi/ARB/MRA and early SGLT2i initiation were independently associated with lower in-hospital mortality (OR 0.12, 95% CI: 0.05–0.25; p < 0.001 and OR 0.27, 95% CI: 0.07–0.96; p = 0.04, respectively). Conclusions Together with traditional medical treatment, initiating SGLT2i within 24 hours of admission for acute myocardial infarction was independently associated with lower in-hospital mortality. These findings suggest a potential association between early SGLT2i use and improved in-hospital outcomes and warrant further investigation in prospective randomized studies.